Perilaku Ibu dalam Memberikan Pendidikan Seks Usia Dini pada Anak Pra Sekolah (Studi Deskriptif Eksploratif di TK IT Bina Insani Kota Semarang) - Astri Aprilia (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Sex educationislearning, realizing, and providing information about sex. The information which is provided includes knowledgeaboutthe function ofthe reproductive organ sby applying morals, ethics, commitment, faithto prevent